THE GROWTH OF SORGHUM TYPES (Sorghum bicolor L. Moench) TREATED ORGANIC FERTILIZER IN DRYLAND - Syahrul; Muamar Kadafi; Ayu Purnamasari; Alfassabiq Khairi (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2024)
Sumbawa Regency exhibits relatively dry soil characteristics due to limited water availability resulting from low rainfall levels. One of the plants suitable for cultivation in this area is sorghum. Sorghum is a viable alternative to rice and corn, as its seed market price is comparatively high. In addition to the limited rainfall in this region, farmers have faced challenges in optimizing crop yields to meet the nutritional needs of their plants. One approach is to optimize the utilization of inorganic and organic fertilizers as supplementary complex plant nutrients. The proposed approach involves using appropriately dosed organic fertilizers, which is anticipated to diminish reliance on excessive inorganic fertilizers. This study aimed to determine the effect of different doses of organic fertilizers on various varieties of sorghum in dryland plantations located in Sumbawa Regency. The experimental design used was Split Plot Design, with sorghum varieties (Bioguma, GBE Methane, and Sweetbetty) as the main-plot and organic fertilizer doses (0, 50, 100, and 200 g/plant) as sub-plots. The results of this study indicated that the interaction between varieties and organic fertilizers on plant growth promotes an increase in plant height, stem diameter, number of leaves, and leaf length. At the end of the plant height observation (42–49 days after sowing), the combination of treatments resulted in an increase in plant height. During the initial growth phases, certain variables showed responses in terms of leaf quantity (7 and 28 days after sowing) and leaf length (14–28 days after sowing). Sweetbetty and GBE Methane show enhanced plant growth; Sweetbetty shows higher plant height and leaf quantity, whereas GBE Methane demonstrates optimal stem diameter and leaf length, compared to Bioguma (a variety from Indonesia